Ants recognize foes and not friends - Guerrieri, Fernando J. (The Royal Society, 2009)
Discriminating among individuals and rejecting non-group members is essential for the evolution and stability of animal societies. Ants are good models for studying recognition mechanisms, because they are typically very efficient in discriminating ‘friends’ (nest-mates) from ‘foes’ (non-nest-mates). Recognition in ants involves multicomponent cues encoded in cuticular hydrocarbon profiles. Here, we tested whether workers of the carpenter ant Camponotus herculeanus use the presence and/or absence of cuticular hydrocarbons to discriminate between nest-mates and non-nest-mates. We supplemented the cuticular profile with synthetic hydrocarbons mixed to liquid food and then assessed behavioural responses using two different bioassays. Our results show that (i) the presence, but not the absence, of an additional hydrocarbon elicited aggression and that (ii) among the three classes of hydrocarbons tested (unbranched, mono-methylated and dimethylated alkanes; for mono-methylated alkanes, we present a new synthetic pathway), only the dimethylated alkane was effective in eliciting aggression. Our results suggest that carpenter ants use a fundamentally different mechanism for nest-mate recognition than previously thought. They do not specifically recognize nest-mates, but rather recognize and reject non-nest-mates bearing odour cues that are novel to their own colony cuticular hydrocarbon profile. This begs for a reappraisal of the mechanisms underlying recognition systems in social insects.